Perancangan Sistem Dashboard Pemantau Produktivitas secara Real-Time pada Mesin CNC di PT X - Ni Luh Saddhwi Saraswati Adnyani; Gregorius Bayu Candra Kirana; Fikri Abdulhakim (Department of Electrical Engineering, UNJANI, 2025)
PT X is a contract manufacturing company that produces metal-based items and has established contracts with several manufacturers, resulting in variations in item demand. The demand for all items can be met through the company’s four departments: cutting, milling, Computer Numerical Control (CNC), and press. Among these departments, the CNC department recorded the lowest productivity percentage in 2023. This was due to the absence of tools or dashboards capable of monitoring CNC machine conditions in real time. To address this issue, a dashboard system was designed to monitor the productivity of CNC machines. The design method used in this study is the Vilarinho method, which begins with diagnosing the productive area, followed by planning and identifying system requirements, developing the system, and concluding with system testing and implementation. The dashboard system was developed using Node-Red software and implemented directly on two CNC machines. The dashboard includes a display that presents data and information reflecting the productivity of CNC machines at PT X. This dashboard will serve as a tool for monitoring and decision-making for both managerial staff and production personnel regarding the CNC machine production process.